‘Before others’: construction pioneers in the uplands of northwestern Laos - Stolz, Rosalie (Social anthropology, 2021)
Given that houses have become a key signifier of an orientation towards the future, several villagers in Pliya can be regarded or regard themselves as pioneers of the construction of a new type of house. I will suggest here that the construction of new concrete houses is not to be understood merely as an adoption of lowland styles but as a self-conscious and selective use of a style of building. Those who are pioneering these houses also discuss their efforts in terms of pioneering acts, emphasising the self-taught nature of their appropriation of new aspects of craftsmanship. Drawing on long-term fieldwork among the Khmu of Pliya, and especially on more recent fieldwork in 2019 and 2020, I wish to argue that the way in which new houses have entered the local cosmos and are materialised by pioneering builders highlights a pioneering ethos that infuses local attempts at future-making, from wet rice cultivation to concrete villas.
Gesehen am 11.11.2021